Home-based palliative care management: what are the useful resources for general practitioners? a qualitative study among GPs in France - Carol-Anne Boudy; Tiphanie Bouchez; Didier Caprini; Isabelle Pourrat; Stéphane Munck; Adriaan Barbaroux (BMC Family Practice, 2020)
Abstract Background Most French people (71%) would like to die at home, but only one out of four actually do. While the difficulties inherent in the practice of home-based palliative care are well described, few studies highlight the resources currently used by general practitioners (GPs) in real life. We have therefore sought to highlight the resources actually used by GPs providing home-based palliative care. Methods Twenty-one GPs of different ages and practice patterns agreed to participate to this qualitative study based upon semi-structured interviews. They were recruited according to a purposive sampling. Transcripts analysis was based upon General Inductive Analysis. Results The resources highlighted have been classified into two main categories according to whether they were internal or external to the GPs. The internal resources raised included the doctor’s practical experience and continuous medical education, personal history, work time organization and a tacit moral contract related to the referring GP’s position. External resources included resource personnel, regional assistance platforms and health facilities, legislation. Conclusion This study provides a simple list that is easy to share and pragmatic solutions for GPs and policymakers. Home-based palliative care practice can simultaneously be burdensome and yet a fulfilling, meaningful activity, depending on self-efficacy and professional exhaustion (burnout), perhaps to a greater extent than on medical knowledge. Home-based palliative care promotion is a matter of social responsibility. The availability of multidisciplinary teams such as regional assistance platforms and Hospitalization at Home is particularly important for the management of palliative care. Policymakers should consolidate these specific resources out of hospitals, in community settings where the patients wish to end their life.